Pengaruh Firm Size dan Market to Book Ratio terhadap Return Portofolio - Dormauli Justina (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2017)
Tujuan penelitian – To examine effect of firm size and market to book ratio on portfolio return.Desain/Metodologi/Pendekatan – Research sample consists of manufacture firm stock listed in Indonesian Stock Exchange 2011-2013. Portfolio return measured by excess return of average 5 highest return and 5 lowest return. Portfolio firm size measured by differences of average return of 5 biggest firm size with 5 smallest firm size. Portfolio book to market ratio measured by differences of average return of 5 highest book to market ratio with 5 lowest book to market ratioTemuan – Based on regression analysis, firm size and book to market ratio have negative effect on portfolio return. The result confirms existence of three factor model in return determination. Investor captures the size effect and financial distress indication of book to market ratio in return estimation and stock investment decision making.Keterbatasan penelitian – This research only used manufacture firm as sample, so the result could not be generalized to all firm population at Indonesia Stock Exchange. This research also did not separate between active stock and inactive stock which were traded monthly, so it probably there was bias return calculation because of the inactive stock.Originality/value – the high of book to market ratio showed that the firm had bad performance and tend to financial distress or poor prospect.